Association of Vascular Endothelial Growth Factor (VEGF) and Mammalian Target of Rapamycin (mTOR) with Radiotherapy Response in High-Grade Sarcomas - Eny Soesilowati; Afiati Afiati; Herry Yulianti; Bethy Suryawathy Hernowo; Adji Kusumadjati (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Sarcoma is a rare malignant aggressive tumor originating from mesenchymal elements. High-grade sarcoma has a poor prognosis. The mortality rate of high-grade sarcomas is 50–75%. Radiotherapy is needed in high-grade sarcoma. Radioresistance in the high-grade sarcoma is still common. Vascular endothelial growth factor (VEGF) and mammalian target of rapamycin (mTOR) are molecular markers that play a role in radioresistance. This study aimed to analyze the association of VEGF and mTOR with radiotherapy response in high-grade sarcoma. Method: This study was an analytic observational study with a cross-sectional design. The minimum samples based on Lameshow’s formula included 40 selected paraffin-embedded tissue blocks from biopsy high-grade sarcoma, consisting of 20 samples of radioresistance and 20 samples of radiosensitive. Immunohistochemistry staining for VEGF and mTOR were performed on all samples. Statistical analysis used the Chi-Square test. The significance of the data was obtained when p-value <0.05.Result: High immunoexpression of VEGF (OR = 17, p < 0.05) and mTOR in high-grade sarcoma showed a significant association with radiotherapy response (OR = 16, p < 0.05). The stepwise logistic regression analysis revealed that both VEGF and mTOR immunoexpression influenced radiotherapy response simultaneously. Conclusion: In this study, which used a minimum sample, it can be concluded that the higher VEGF and mTOR immunoexpression showed the higher radioresistance in high-grade sarcoma.